Role of Prestenting Versus Non Prestenting in Outcomes of Retrograde Intrarenal Surgery in Renal Stones - Shah, Rajiv; Khanal, Sandeep; Khadka, Deepesh; Adhikari, Kapil (Journal of College of Medical Sciences-Nepal, 2021)
Background To find out outcomes of patients who underwent retrograde intrarenal surgery with a ureteral access sheath and without ureteral access sheath in renal stones. Methods This is the prospective comparative study of seventy patients who underwent retrograde intrarenal surgery of renal stones ≤2 cm conducted at Chitwan Medical College, Bharatpur 10, Nepal between August 05, 2023 to February 04 2024 with a convenience sampling method Ethical approval was obtained from Institutional Review Committee (Reference number: CMC-IRC/080/081-110). The patients age, sex, stone characteristics, operative time, post operative complications, stone free rate and hospital stay are compared between the Prestenting and Non Prestenting groups. Results The mean age of the patients in pre stenting group is 50.31years with standard deviation of 17.29 while in non Prestenting group is 45.55 years with standard deviation of 17.62 with no significant p value. The duration of operation time in Prestenting group is 69.06 minutes with standard deviation of 2.71 to that of 73.63 minutes with standard deviation of 6.88 which shows a significant p value. The stone free rate of Prestenting group is 90.62% while 86.84% in non Prestenting group with no significant p value. Conclusions The role of Prestenting in renal stones only decreases the operation time by facilitating the access sheath comfortably with no other significant differences.